Women, enclosure and estate improvement in eighteenth-century Northamptonshire - McDonagh, Briony (Cambridge University Press, 2009)
This paper examines the role of elite women in estate management, enclosure and landscape improvement in eighteenth-century England, a topic which has to date received little in the way of sustained academic consideration. The paper focuses on four women who took control of sizeable Northamptonshire estates in the 1760s and early 1770s, and demonstrates that these women were active as both managers and innovators. In examining the women’s involvement in estate management, the paper explores a series of important questions about women’s place in the history of parliamentary enclosure and landscape improvement, as well as women’s role in eighteenth-century society more generally.